Dual kidney transplant techniques: A systematic review. Issue 8 (23rd June 2017) - Cocco, Annelise; Shahrestani, Sara; Cocco, Nicholas; Hameed, Ahmer; Yuen, Lawrence; Ryan, Brendan; Hawthorne, Wayne; Lam, Vincent; Pleass, Henry
Abstract: Background: Dual kidney transplantation (DKT) was developed to improve outcomes from transplantation of extended criteria donors (ECD). This study examined which surgical techniques have been reported for DKT and whether any technique had superior patient and graft survival. Method: Electronic databases were searched for published studies mapping to MESH terms: "kidney or renal" AND "transplan*" AND "dual or double." Single case reports, studies of patients less than 18 years old, studies which did not describe the surgical technique, and studies that did not report patient or graft survival were excluded. Results: Fifteen reports of 434 DKT recipients were identified. Three techniques were described: bilateral placement; unilateral placement with separate anastomoses; and unilateral placement with patch anastomoses. Patient survival across all three techniques was over 95% at 1 year, and graft survival was also similar at over 90%. Rates of delayed graft function were between 20% and 30% across all techniques. Conclusion: The three techniques have equivalent delayed graft function as well as patient and graft survival rates. This is an encouraging result as it means that the surgeon can choose to use the technique which is most appropriate for their own skills and for the patient.